IFRS adoption, corporate governance and faithful representation of financial reporting quality in Nigeria's development banks - Ayodeji T. Ajibade; Nelson Okutu; Folorunsho Akande; Jerry D. Kwarbai; Ifayemi M. Olayinka; Ayooluwa Olotu (Cogent Business & Management, 2022)
Development banks were designed to achieve the government's economic priorities that were not adequately addressed by the banking industry. Studies, however, show that the activities of some development banks in Nigeria have not been as impacting as expected for different reasons, which include lack of access to finance. This study investigated the impact of International Financial Reporting Standards (IFRS) adoption and corporate governance on the faithful representation of the financial reporting quality in Nigeria's development banks. The study adopted a survey research design. The study adopted a convenience sampling technique. The validity and reliability test of the instrument was conducted on the variables. The reliability test was analyzed using Cronbach's alpha test, and all variables were greater than 0.7, indicating a good construct. The study used descriptive and inferential (multiple linear regression) data analysis methods. The study's findings revealed that IFRS adoption and Corporate governance significantly affect the faithful representation of financial reporting of Nigeria's Development Banks. The study concluded that IFRS adoption and corporate governance significantly affect the faithful representation of the financial reporting quality in Nigeria's development banks. The paper recommended that the management of the development banks should endeavor to take advantage of the opportunities presented by the IFRS adoption to improve their reporting to promote uniformity and transparency.
Keywords: 650; corporate governance; faithful representation; financial reporting quality; IFRS adoption; Nigeria's development banks